Legal Protection on Franchise as Business Alternative Development - Hartanto Hartanto; Erna Tri Rusmala Ratnawati (Faculty of Law, University of Mataram, 2020)
The growth of franchise has developed rapidly and demanded by the franchisee and franchisor, since this system containing a symbiosis mutualism where the parties are bound to each other and gain a lot of advantages. However, this systemarisesthe questions: what is the basic consideration for the franchisee before agree in the franchise agreement? What is the requirement which needs to be listed in the franchise agreement? What is the excellence of franchise as the business alternative for the franchisee?The research method of this article is legal research or also called doctrinal research which purposes to analyze the regulation on franchise business which is descriptive, this research using a conceptual/normative approach which is a research that collecting secondary data such as primary, secondary, and tertiary legal materials. Before the parties entering a franchise agreement, the franchisee must be doing some survey on the feasibility of the franchise to know and analyzing where the result will become a consideration in the decision making for the franchisee. The franchisee should be paying attention to the criteria of the franchise if it is worth buying or as partner cooperation and take into account the criminal aspect on the franchise management.